Factors Influencing Cervical Cancer Screening: A Cross‐Sectional Study Among Ethnically Diverse Women in the Kumasi Metropolis of Ghana - Abdul‐K. Abubakari; Janet Gross; Ibrahim D. Kwaku; Isaac K. Boateng (Health Science Reports)
ABSTRACT Background Globally, Ghana is one of the countries with the greatest cervical cancer (CC) burdens and mortality rates. Available research has focused primarily on women's experiences in the general population neglecting factors that influence cervical cancer screening (CCS) among ethnically diverse populations in Ghana. Aim This study explored the factors influencing CCS among ethnically diverse women in the Kumasi Metropolis of Ghana. Method From April to June 2023, a community‐based cross‐sectional study was carried out in the Aboabo and Asawase communities of the Ashanti Region. Binary and multivariable logistic regressions were employed to determine the relationships between the dependent and independent variables. Outcome variables with p‐values < 0.05 were considered statistically significant. Results Habits, knowledge, perceived benefits, and facilitating factors influenced CCS among ethnically diverse women. An overall self‐reported CCS rate of 7.2% (n = 32) with an early age of sexual initiation of 15–20 years was recorded. While habits (OR = 0.23, 95% CI 0.09, 0.58; p = 0.002), affect (OR = 0.00, 95% CI 0.00, 0.03; p < 0.001), and the perceived benefits of screening (OR = 3.07, 95% Cl 1.01, 10.8; p = 0.059) were associated with CCS. Norms (OR = 0.00, 95% CI 0.00, 20,948,726,859,075; p > 0.9), knowledge (OR = 1.27, 95% CI 0.61, 2.53; p = 0.5), and facilitating factors (OR = 1.02, 95% CI 0.51, 2.01; p > 0.9) were not statistically significant with CCS. Conclusion Poor knowledge, lower perceived benefits of CCS, and weak facilitating factors were identified as barriers to CCS. Implementing national CCS and vaccination campaigns to improve awareness, and screening to reduce women's risk is encouraged.